2000
DOI: 10.1074/jbc.275.14.10342
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Abolishes the Mammalian G2/M DNA Damage Checkpoint by Inhibiting Ataxia-Telangiectasia-mutated Kinase Activity

Abstract: Recent evidence indicates that arrest of mammalian cells at the G 2 /M checkpoint involves inactivation and translocation of Cdc25C, which is mediated by phosphorylation of Cdc25C on serine 216. Data obtained with a phospho-specific antibody against serine 216 suggest that activation of the DNA damage checkpoint is accompanied by an increase in serine 216 phosphorylated Cdc25C in the nucleus after exposure of cells to ␥-radiation. Prior treatment of cells with 2 mM caffeine inhibits such a change and markedly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
182
2
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(189 citation statements)
references
References 30 publications
3
182
2
1
Order By: Relevance
“…Previous studies had indicated that caffeine inhibited ATM and ATR signaling in checkpoints acting in G1, S and G2 [2,41,51]. We were not surprised therefore to find that caffeine fully abrogated ATM-and ATR-dependent S and G2 checkpoint responses in IRand UVC-treated human fibroblasts.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Previous studies had indicated that caffeine inhibited ATM and ATR signaling in checkpoints acting in G1, S and G2 [2,41,51]. We were not surprised therefore to find that caffeine fully abrogated ATM-and ATR-dependent S and G2 checkpoint responses in IRand UVC-treated human fibroblasts.…”
Section: Discussionmentioning
confidence: 61%
“…Inactivation of either enzyme attenuates the G2 checkpoint response by about 50%. The full ablation by caffeine of G2 checkpoint response has been attributed to its inhibition of ATM [41]. A recent publication disputes the interpretation that ATM and ATR are directly inhibited by caffeine in cultured cells [42].…”
Section: Caffeine Inhibits G2 Checkpoint Functionmentioning
confidence: 99%
“…34 Caffeine is capable of abrogating cell cycle check points, thereby releasing cells from DNAdamaged evoked G 2 -arrest. 40 Although caffeine reversed IR-induced G 2 /M arrest in RD cells, it did not prevent ceramide-mediated G 2 -arrest. Given the lack of phosphorylation of components of the DNA damage pathway (ATM, Chk1 and Chk2; Supplementary Figure 1) and no evidence of double-strand breaks (a-Histone H2A.X phosphorylation, Ser319), our data precludes ceramide-induced G 2 -arrest and stabilization of p21 Cip1/Waf1 protein expression to be a result of DNA damage.…”
Section: Discussionmentioning
confidence: 93%
“…In response to ionising radiation (IR), threonine 68 of CHK2 is rapidly phosphorylated by ataxia telangiectasia mutated (ATM) (Matsuoka et al, 2000;Zhou et al, 2000), allowing oligomerisation and transautophosphorylation of CHK2 (Ahn et al, 2002;Xu et al, 2002). Activated CHK2 is involved in maintaining the G1/S and G2/M checkpoints by phosphorylation of CDC25A, CDC25C and p53 (Chaturvedi et al, 1999;Shieh et al, 2000;Falck et al, 2001), and repair of double-strand DNA breaks via homologous recombination (HR) through phosphorylation of BRCA1 (Lee et al, 2000).…”
mentioning
confidence: 99%